2017
DOI: 10.1055/s-0037-1606571
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Rectal Perforation Presenting as Peritonitis in a Child with Enteric Fever

Abstract: Typhoid fever is common in developing countries. It may lead to bowel perforation. Terminal ileum is the most frequent site of perforation. However, perforation at uncommon sites such as rectosigmoid junction may occur occasionally. In this study we report a patient who we treated for perforation peritonitis; on exploratory laparotomy, it turned out to be a rectal perforation. The patient was operated successfully. As an unusual presentation, it is being reported with a review of the relevant literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In our study, we found 8/13 cases of ileal perforation and one case of acute intestinal obstruction with impending multiple ileal perforations; if we include this as perforation, total 9/13 cases of ileal perforation and four cases of atypical sites of perforation. Review of relevant literature during our study revealed sporadic case reports of multiple typhoid, ileal and cecal perforations [12]; few cases of Caecal [14], sigmoid [15] and rectal [16] perforation but typhoid gastric perforation could not be found. Also, there is no reporting of combined jejunoileal perforations along with Meckel's band obstruction and Meckel's diverticular perforation.…”
Section: Discussionmentioning
confidence: 69%
“…In our study, we found 8/13 cases of ileal perforation and one case of acute intestinal obstruction with impending multiple ileal perforations; if we include this as perforation, total 9/13 cases of ileal perforation and four cases of atypical sites of perforation. Review of relevant literature during our study revealed sporadic case reports of multiple typhoid, ileal and cecal perforations [12]; few cases of Caecal [14], sigmoid [15] and rectal [16] perforation but typhoid gastric perforation could not be found. Also, there is no reporting of combined jejunoileal perforations along with Meckel's band obstruction and Meckel's diverticular perforation.…”
Section: Discussionmentioning
confidence: 69%
“…In our patient’s case, the perforation occurred in the antimesenteric surface of rectum, which is rare in children. However, there is a report of isolated rectal perforation in a 3-year-old girl with enteric fever [ 12 ].…”
Section: Discussionmentioning
confidence: 99%